2021
DOI: 10.1002/ijc.33459
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation markers for cancer risk prediction of vulvar intraepithelial neoplasia

Abstract: Current clinical and histological classifications are unable to determine the risk of vulvar squamous cell carcinoma (VSCC) in high‐grade vulvar intraepithelial neoplasia (VIN), making prognostic biomarkers highly needed. We studied host‐cell DNA methylation markers in high‐grade squamous intraepithelial lesion (HSIL) and differentiated VIN (dVIN) without VSCC, in HSIL and dVIN adjacent to VSCC and in human papillomavirus (HPV) positive and negative VSCC, relative to control vulvar tissues. A series of 192 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
3
20
0
1
Order By: Relevance
“…Moreover, dVIN has a greater risk for malignant transformation compared to vulvar HSIL [31] with a 10-year risk of malignant transformation of 9.7% for vulvar HSIL compared to 50% of dVIN [32], and the presence of lichen sclerosus and dVIN adjacent to VSCC leads to a significantly worse prognosis [33]. It has recently been suggested that higher DNA methylation levels in VIN (both dVIN and vulvar HSIL) is related with increased disease severity and, consistent with this finding, VIN adjacent to VSCC showed a similar high-methylation pattern to VSCC [34]. The presence of lichen planus is a controversial issue-some authors suggest that in the presence of lichen planus is associated with more HSIL recurrences [35]; furthermore, in the case of coexistence with VSCC, these tumors show a more aggressive biological behavior with greater lymph node involvement, greater number of loco-regional relapses, and lower survival [36] compared with VSSC not associated with lichen planus.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, dVIN has a greater risk for malignant transformation compared to vulvar HSIL [31] with a 10-year risk of malignant transformation of 9.7% for vulvar HSIL compared to 50% of dVIN [32], and the presence of lichen sclerosus and dVIN adjacent to VSCC leads to a significantly worse prognosis [33]. It has recently been suggested that higher DNA methylation levels in VIN (both dVIN and vulvar HSIL) is related with increased disease severity and, consistent with this finding, VIN adjacent to VSCC showed a similar high-methylation pattern to VSCC [34]. The presence of lichen planus is a controversial issue-some authors suggest that in the presence of lichen planus is associated with more HSIL recurrences [35]; furthermore, in the case of coexistence with VSCC, these tumors show a more aggressive biological behavior with greater lymph node involvement, greater number of loco-regional relapses, and lower survival [36] compared with VSSC not associated with lichen planus.…”
Section: Discussionsupporting
confidence: 53%
“…DNA methylation signatures have emerged as promising biomarkers in oncology capable of measuring risk factor exposure [ 35 , 46 , 47 ], discriminating different types of primary tumors [ 48 , 49 ], predicting the progression of preneoplastic lesions [ 50 , 51 ], predicting response to treatment and prognosis [ 35 , 52 , 53 , 54 ], and even detecting malignant tumors years before conventional diagnosis [ 55 ]. Although different DNA methylation signatures are usually assessed for different tissues and outcomes, a common feature of cancers is global hypomethylation [ 17 , 56 , 57 ], in general associated with poor OS [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for comprehensive understanding of the carcinogenesis, characterization of epigenetic changes is also crucial. Unfortunately, for VSCC these changes have been interrogated in only a few studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that ZIC1 was hyper-methylated in both subtypes of VSCC, indicating an involvement of this gene in the HPV-independent pathway of VSCC carcinogenesis as well. A recent study reported an association between increasing methylation levels of ZIC1 and the risk of progression of VIN to VSCC [ 40 ]. One of the hyper-methylated DMGs in our study, DNMT3A , has been previously detected in VSCC, and was reported to correlate with a risk of recurrence [ 37 ].…”
Section: Discussionmentioning
confidence: 99%